2002
DOI: 10.1007/s00259-002-0785-6
|View full text |Cite
|
Sign up to set email alerts
|

Self-stunning in thyroid ablation: evidence from comparative studies of diagnostic 131I and 123I

Abstract: Twenty-six patients who had undergone recent surgery for differentiated thyroid cancer were investigated using iodine-131 iodide (120 MBq). Uptake in the thyroid bed was measured at 3 days using a dual-head gamma camera. An ablation activity of 131I iodide (4,000 MBq) was administered 3-38 (median 14) days later and uptake in the thyroid bed measured once or twice, 1-3 days post therapy. For measurements post therapy, the gamma camera was operated in the high-count rate mode with appropriate correction factors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
56
1
3

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(64 citation statements)
references
References 3 publications
4
56
1
3
Order By: Relevance
“…Therefore, it is not surprising that radiation-induced loss of iodide transport develops gradually and rather slowly after the NIS gene transcription is significantly suppressed. Moreover, these in vitro findings support the many clinical reports of a delay in detection of stunning until several days after the administration of radioiodine for diagnostic purposes (1)(2)(3)(4)(5)(6)(7)36,37).…”
Section: Discussionsupporting
confidence: 72%
See 2 more Smart Citations
“…Therefore, it is not surprising that radiation-induced loss of iodide transport develops gradually and rather slowly after the NIS gene transcription is significantly suppressed. Moreover, these in vitro findings support the many clinical reports of a delay in detection of stunning until several days after the administration of radioiodine for diagnostic purposes (1)(2)(3)(4)(5)(6)(7)36,37).…”
Section: Discussionsupporting
confidence: 72%
“…To avoid this problem, 123 I has been proposed to replace 131 I for diagnostic uptake measurements. Stunning has nevertheless occurred in thyroid remnants and metastases after administration of 123 I within a rather wide range of diagnostic activities (50-200 MBq) (7,12,13). However, whether 123 I irradiation triggers cellular changes leading to loss of NIS expression and reduced iodide uptake has not been experimentally investigated.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…They concluded that I-131 ablation has the same outcome whether (2 mCi) 74 MBq of I-131 used as a diagnostic agent or (400 µCi) 14.8 MBq of I-123 used for imaging prior to I-131 ablation. Although these conflicting results could be attributed to the fact that iodide transport and NIS messenger RNA (NIS mRNA) expression were reduced by both I-131 and I-123 (29) , the stunning observed following I-123 could not be explained by errors in the estimation of relative uptake due to different tissue absorption of the I-131 and I-123 photons, nor by the radiation dose delivered by the I-123 (30) . The resultant radiation dose to the thyroid remnant, as the therapeutic radioiodine is being taken up, may be sufficient to inhibit the uptake process, thus leading to a reduction in maximum uptake when compared with that of a diagnostic activity of radioiodine (30) .A unique advantage of this study is that it is one of a few studies that compared outcome of I-131 ablation in age-, gender-, histopathology-matched patient groups following either post-thyroidectomy I-123 or I-131WBS.…”
Section: Discussionmentioning
confidence: 86%
“…In cases of therapy of the thyroid and its tumors, it is of course very important to keep in mind that pre-therapeutic contamination with (non-radioactive) iodine leads to diminished uptake of the radioiodine not only by competitive inhibition of the iodine transporter (similarly to a blockade of a receptor), but also through a specifi c arrest of thyreocytes (phenomenon referred to as Wolff-Chaikoff-effect) [26]. An issue of changing the maximal uptake and/or effective half time by irradiation of the target tissue (even during the dosimetry measures) is controversial, but also exists [27][28][29]. These observations may lead to avoiding errors in radionuclide therapy and to its further optimization.…”
Section: Effective Half Timementioning
confidence: 99%